Gestión del conocimiento y efectividad organizacional en municipalidades de la provincia de San Martín, Perú - Santa Cruz Malon , Adan (2021)
The purpose of the research was to determine the relationship between knowledge management (KM) on organizational effectiveness (EO) in the public sector. The sample consisted of 220 collaborators from the district municipalities of Morales, Tarapoto and La Banda de Shilcayo in the San Martín region. Two questionnaires were used to collect the data. The validity of the instruments was developed through expert judgment, for which it requested the analysis of the items regarding their clarity, congruence, context and domain of the construct, by three experts; who gave their assessment on the content validity of the questionnaires. On the other hand, the reliability of the instruments was obtained through the Cronbach's alpha index in a pilot sample of 15 study units. For the knowledge management scale, a Cronbach's alpha of 0.960 was obtained; while for the organizational effectiveness scale, this index had a value of 0.924. It was found that the variables knowledge management and organizational effectiveness are at a frequent development level, that is, the entities have implemented adequate knowledge management, which results in adequate organizational effectiveness; their percentages being 50% and 64% respectively. On the other hand, a mean relationship was obtained between both variables (Rho: 0.500 and p-value: 0.000).